Whole-genome resequencing of Cucurbita pepo morphotypes to discover genomic variants associated with morphology and horticulturally valuable traits. Issue 1 (11th August 2019) - Xanthopoulou, Aliki; Montero Pau, Javier; Mellidou, Ifigeneia; Kissoudis, Christos; Blanca, José; Picó, Belén; Tsaballa, Aphrodite; Tsaliki, Eleni; Dalakouras, Athanasios; Paris, Harry S; Ganopoulou, Maria; Moysiadis, Theodoros; et al.
Abstract: Cucurbita pepo contains two cultivated subspecies, each of which encompasses four fruit-shape morphotypes (cultivar groups). The Pumpkin, Vegetable Marrow, Cocozelle, and Zucchini Groups are of subsp. pepo and the Acorn, Crookneck, Scallop, and Straightneck Groups are of subsp. ovifera . Recently, a de novo assembly of the C. pepo subsp. pepo Zucchini genome was published, providing insights into its evolution. To expand our knowledge of evolutionary processes within C. pepo and to identify variants associated with particular morphotypes, we performed whole-genome resequencing of seven of these eight C. pepo morphotypes. We report for the first time whole-genome resequencing of the four subsp. pepo (Pumpkin, Vegetable Marrow, Cocozelle, green Zucchini, and yellow Zucchini) morphotypes and three of the subsp. ovifera (Acorn, Crookneck, and Scallop) morphotypes. A high-depth resequencing approach was followed, using the BGISEQ-500 platform that enables the identification of rare variants, with an average of 33.5X. Approximately 94.5% of the clean reads were mapped against the reference Zucchini genome. In total, 3, 823, 977 high confidence single-nucleotide polymorphisms (SNPs) were identified. Within each accession, SNPs varied from 636, 918 in green Zucchini to 2, 656, 513 in Crookneck, and were distributed homogeneously along the chromosomes. Clear differences between subspecies pepo and ovifera in genetic variation and linkage disequilibrium are highlighted. In fact, comparison between subspecies pepo and ovifera indicated 5710 genes (22.5%) with Fst > 0.80 and 1059 genes (4.1%) with Fst = 1.00 as potential candidate genes that were fixed during the independent evolution and domestication of the two subspecies. Linkage disequilibrium was greater in subsp. ovifera than in subsp. pepo, perhaps reflective of the earlier differentiation of morphotypes within subsp. ovifera . Some morphotype-specific genes have been localized. Our results offer new clues that may provide an improved understanding of the underlying genomic regions involved in the independent evolution and domestication of the two subspecies. Comparisons among SNPs unique to particular subspecies or morphotypes may provide candidate genes responsible for traits of high economic importance.